2010
DOI: 10.1017/s1751731109991376
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary laminarin and fucoidan in the diet of the weanling piglet on performance, selected faecal microbial populations and volatile fatty acid concentrations

Abstract: A 2 3 2 factorial experiment (n 5 12 replicates per treatment, 4 pigs per replicate) was performed to investigate the effects of seaweed extracts, laminarin (derived ß-glucans) and fucoidan (sulphated polysaccharides), independently or in combination on post-weaning piglet performance and selected microbial populations. At weaning, the piglets (24 days of age, 6.4 kg live weight) were assigned to one of the four dietary treatments: (T1) basal diet, (T2) basal diet with 300 p.p.m. laminarin, (T3) basal diet wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 34 publications
6
104
3
1
Order By: Relevance
“…The majority of research to date focused primarily on dietary manipulation postweaning reported improvements in piglet performance (Gahan et al, 2009), intestinal microfiora composition (McDonnell et al, 2010;O'Doherty et al, 2010), and immune status (Reilly et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research to date focused primarily on dietary manipulation postweaning reported improvements in piglet performance (Gahan et al, 2009), intestinal microfiora composition (McDonnell et al, 2010;O'Doherty et al, 2010), and immune status (Reilly et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These results are also similar to the ones obtained by Walsh et al (2014). Moreover, a favourable effect has also been observed when supplementing feed of pre farrow sows with seaweed extracts, showing a better production performance for the post weaning piglets (McDonnell et al 2010). This better performance may be attributed to better intestinal flora, which was demonstrated in Gardiner et al (2008), who worked with Ascophyllum nodosum extract in fattening animals.…”
Section: Discussionmentioning
confidence: 92%
“…Deville et al (2007) reported that dietary polysaccharides from seaweed inhibit the adhesion and can influence the translocation of pathogenic microorganisms across the intestinal wall. McDonnell et al (2010) formulated a basal diet with 300 ppm laminarin, 240 ppm fucoidan, and a combination of laminarin and fucoidan in that ratio and offered it to pigs for 21 days. Smith et al (2011) optimized the inclusion level of purified laminarin from L. digitata seaweed and observed its effect on piglet performance, selected bacterial populations, volatile fatty acid production, and cytokine and mucin gene expression in the porcine ileum and colon.…”
Section: Sow and Pigletsmentioning
confidence: 99%